Nutritional Evaluation of Extruded-Expeller Soybean Meal (EESBM) as a New Feed Ingredient for Modern Broilers - S. Mukesh, R.Kavitha; A. Natarajan; K. Rajendran (Indian Journal of Animal Nutrition, 2024)
This study evaluates the potential of extruded and expeller soybean meal (EESBM) compared to solvent-extracted soybean meal (SESBM) as a feed ingredient in broiler diets. Chemical composition, fatty acid profile and in vitro protein quality assays were conducted on collected samples. EESBM demonstrated significantly higher dry matter (96.07 per cent) and ether extract (6.77 per cent) content, with a notable DM per cent advantage (96.07per cent versus 88.63 per cent) over SESBM. EESBM’s crude protein (46.39 per cent) content was slightly higher than the EESBM (45.56 per cent). Calculated gross energy and metabolizable energy values of EESBM were significantly higher (4688.50 and 2661.08 kcal/kg) than SESBM (4361.83 and 2199.36 kcal/kg), primarily attributed to increased EE content in EESBM. KOH solubility and PDI values showed marginal differences, with EESBM exhibiting higher linolenic acid (7.86 per cent) and lower levels of palmitic acid, stearic acid, arachidic acid and behenic acid compared to SESBM. Urease activity in terms of pH unit change was comparable. Based on this study the EESBM is proved to be a novel ingredient over SESBM in terms of its quality.